Peer Learning and Research Culture Within Student Organizations in Engineering: Students' Perceptions - Galantini Velarde, K.; Cáceres Montero, L.; Pachas, A. (Journal of Engineering Education Transformations, 2025)
Learning-centered models require using interactive methods, such as peer learning. In this context, student organizations are introduced as groups of students managed as autonomous extracurricular spaces in which they enrich their training process upon practical issues that promote peer learning, while encouraging lifelong learning (LL). Thus, this research explores undergraduate engineering students' perceptions about the influence of student organizations on the promotion of undergraduate research culture through a survey. Results have indicated that 91% of the surveyed students think that research is encouraged within these spaces, and 79% perceive that these organizations have provided them with the necessary support to start a research project. Finally, 87% have begun to consider research as an important factor for their professional development, in accordance with LL. Therefore, it was concluded that the promotion of undergraduate research culture within these organizations strengthens students' intention to develop their final degree project as a research paper.